Late Cenozoic mammalian faunal evolution at the Jinyuan Cave site of Luotuo Hill, Dalian, Northeast China. (10th March 2021) - Jin, Changzhu; Wang, Yuan; Liu, Jinyuan; Ge, Junyi; Zhao, Bo; Liu, Jinyi; Zhang, Hanwen; Shao, Qingfeng; Gao, Chunling; Zhao, Keliang; Sun, Boyang; Qin, Chao; et al.
Abstract: Recently, rich fossiliferous deposits dated to the late Cenozoic have been discovered from Jinyuan Cave at Luotuo Hill, an extremely large-sized cave site situated within in the Dalian Puwan Economic Zone of Dalian Municipality, Liaoning Province in Northeast China. Abundant and diverse vertebrate fossils unearthed from different fossiliferous layers of Jinyuan Cave, a site of enormous size with a sedimentary thickness of over 40 m and its deposits can be roughly divided into three fossiliferous deposit units, altogether containing six fossiliferous layers belonging to different ages from the Late Pliocene to the Middle Pleistocene. Based on a combination of biostratigraphic and geochronological evidence, the fossil assemblages from Jinyuan Cave can be divided into three successive faunas that span the Late Cenozoic (ca. 3.60–0.35 Ma): the Wanghai fauna from upper faunal unit (Middle Pleistocene, 0.78–0.35 Ma), the Jinyuan fauna from middle-lower faunal unit (Early Pleistocene, 2.60–0.78 Ma) and the Luotuoshan fauna of the bottommost faunal unit (Late Pliocene, 3.6–2.6 Ma). The mammalian faunal evolution of Jinyuan Cave can be divided into four temporal stages during the late Cenozoic. The new discovered Jinyuan Cave provides a unique and nearly-continuous faunal and sedimentary sequence stretching from the Late Pliocene to the Middle Pleistocene, hugely significant for establishing the Quaternary Mammal Fauna Sequence of Northeast China for the first time based on a combination of biostratigraphy, geochronology, and for discussing the environmental background.